Nonvolatile resistive switching in metal oxides for the application in resistive random access memory - Peng, Haiyang (2014)
Resistive random access memory (ReRAM or memristor) based on the resistive switching (RS) has been proposed as a potential candidate for next generation nonvolatile memory with high density, fast write and erase access, low power operation, and excellent retention performance. Although most of the transition metal oxides have been reported as the building blocks, the underlying mechanism of the switching is still unclear and controversial, which hinders the further development of ReRAM. The main objective of this dissertation is to report our in-depth scientific research on ReRAM based on transition metal oxides, including the materials preparation and characterization, device fabrication, electrical measurements, and investigation on the mechanisms. The structure of this thesis contains three parts, as follows. First, we explore a few new ReRAM materials and compare its performance with the existing ones. We report the excellent unipolar RS behaviors in spinel ZnMn2O4 and ilmenite ZnMnO3, both of which have ON/OFF ratios larger than 104. Good endurance and retention are achieved in both oxides. The conduction mechanism of the OFF state is attributed to the space-charge-limited conduction. The Ohmic behavior of the ON state suggests a filamentary conduction mechanism. This study introduces two new candidates for nonvolatile resistive random access memory devices, and it indicates that formation and rupture of conducting filaments are universal in certain ternary oxides even though they may possess distinct crystalline structures. Second, based on a well studied material of ZnO, we study the doping and electrode effects on the RS characteristics. We carry out a comparative study on RS in Mn-doped ZnO thin films; samples grown on Pt and Si show unipolar and bipolar switching behaviors, respectively. Fittings of the current-voltage curves reveal the filamentary conduction in Pt/Mn:ZnO/Pt with good data retention. On the other hand, the interfacial effect dominates in Pt/Mn:ZnO/Si, and the low resistance state exponentially relaxes towards the high resistance state. Thus our results suggest that selecting electrodes dictates the RS properties, presumably by affecting the migration dynamics of oxygen vacancies. Finally, using NiO as an example, we demonstrated a controlled room temperature conversions between nonvolatile memory switching and volatile threshold switching within a single device, by rationally adjusting the stoichiometry and the associated defect characteristics. Moreover, from first-principles calculations and x-ray absorption spectroscopy (XAS) experimental studies, we found that the strong electron correlations and the orbital exchange interactions play key deterministic roles in the switching operations.